2020
DOI: 10.35654/ijnhs.v3i5.330
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Application Anemia Management Module On Improving Maternal Behaviors and Hemoglobin Level among Pregnant Women with Anemia

Abstract: Lack of knowledge of mothers on the importance of iron tablet consumption impact on compliance. So that the iron requirement is not fulfilled and the effect of anemia. Countermeasures to raise awareness and behavior to increase hemoglobin levels. Educational modules consisted of information regarding pregnancy and the importance of anemia Fe tablet consumption. The study aimed to examine the effect of the anemia management module to change mothers' behavior in improving hemoglobin levels. A quasi-experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
2
0
4
Order By: Relevance
“…Traditional cultural beliefs affect pregnant women who suffer from anemia since it is revealed that the pregnancy process is substantially influenced by the traditions that have been believed (Kapoh et al, 2021). In addition, in Ethiopian culture, pregnant women should limit the consumption of green leafy vegetables, yogurt, cheese, and sugar cane during pregnancy (Nadziroh et al, 2020). Whereas the Indian people believe that pregnant women should limit the consumption of fruits, vegetables, meat, and eggs because these foods will harm the pregnancy .…”
Section: Obstacle Factorsmentioning
confidence: 99%
“…Traditional cultural beliefs affect pregnant women who suffer from anemia since it is revealed that the pregnancy process is substantially influenced by the traditions that have been believed (Kapoh et al, 2021). In addition, in Ethiopian culture, pregnant women should limit the consumption of green leafy vegetables, yogurt, cheese, and sugar cane during pregnancy (Nadziroh et al, 2020). Whereas the Indian people believe that pregnant women should limit the consumption of fruits, vegetables, meat, and eggs because these foods will harm the pregnancy .…”
Section: Obstacle Factorsmentioning
confidence: 99%
“…In addition, early studies also established that people with a history of infection cause anemia through loss of nutrients, decreasing appetite, decreasing efficiency of absorption, and use of nutrients. Higher prevalence of anemia among women with parasitic infestations due to the same line of reasoning forwarded for infection (Nadiyah et al, 2021).…”
Section: Resultsmentioning
confidence: 95%
“…Pencegahan dan penatalaksanaan anemia pada ibu hamil tidak terlepas dari keterlibatan tenaga kesehatan di fasilitas kesehatan primer meliputi bidan, dokter, Ahli Teknologi Laboratorium Medik (ATLM), apoteker dan nutrisionis. Bidan memiliki peran dalam memberikan pendidikan kesehatan, pemberian TTD (Helmy et al, 2017;Nadziroh et al, 2020) dan menerapkan model four pillars approach (FPA). Model ini meliputi edukasi tentang pola hidup sehat selama hamil, melibatkan suami atau anggota keluarga lainnya, memberikan asuhan kebidanan yang kompeten terkait anemia selama kehamilan serta meningkatkan sikap profesional antar bidan (Widyawati et al, 2015a).…”
Section: World Health Organization (Who) Telah Merekomendasikan Pembe...unclassified